2009
DOI: 10.1589/jpts.21.177
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction Time of Mental Rotation Predicts Strain in Rugby Players

Abstract: Abstract. [Purpose] This study investigated the relation between motor imagery and hamstring strain in rugby players.[Subjects] The participants of this study comprised 21 university rugby players (42 legs).[Methods] The motor imagery capacity of the subjects was evaluated using mental rotation and various motor exercises. The subjects were followed up 6 months after the measurements were taken, and the hamstring strain occurring in the intermittent period was investigated.[Results] Seven legs of 6 players (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Eleven articles54 55 57 59 62 64 69 71 75 80 81 did not report on the reliability and validity of the tests to examine risk factors and subsequently did not score on item 20.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven articles54 55 57 59 62 64 69 71 75 80 81 did not report on the reliability and validity of the tests to examine risk factors and subsequently did not score on item 20.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies55 59 60 62 66 70 73 77 78 8082 did not use adequate adjustment for confounding variables, particularly previous injury and age. Without adequate adjustment for confounding variables, the results of some studies may not be accurate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, mental practice (MP) is the repeated imagination of movements using MI. Motor imagery-based mental practice is commonly used in many fields of neuroscience, such as physical therapy, rehabilitation medicine, sports science, etc [12][13][14] . Many studies have reported that the imagination of performing a motor task improves the ability of the performance and is accompanied by effective processing in the motor learning system 13,15,16) .…”
Section: Introductionmentioning
confidence: 99%